Fabrication of mesoporous Er doped ZnMnO3 nanoflake via sol gel approach for energy storage application. (1st May 2023) - Waheed, Muhammad Suleman; Jabbour, Karam; Houda, Sara; Alzahrani, Fatimah Mohammed A.; Katubi, Khadijah Mohammedsaleh; Riaz, Saira; Ashiq, Muhammad Naeem; Manzoor, Sumaira; Aman, Salma; Al-Buriahi, M.S.
Abstract: In the present study, perovskites have lately garnered considerable interest as potential electrochemical energy storage components. The fabricated ZnMnO3, and doped material (where, Er = 5, 10 and 15%) perovskite materials were fabricated with solgel technique and analyzed as an energy conversion system. Using scanning electron microscopy (SEM), energy dispersive X-rays spectroscopy (EDX) and X-ray diffraction (XRD), the shape, elemental and crystalline phases were determined. Using impedance spectroscopy and electrochemical capacitance analysis, the electrical capacity and impedance were determined. The Er doped ZnMnO3 perovskite resulted in 15% Er doped ZnMnO3 responses the specific capacitance of 1558.41 F g −1 with an energy density of 54.18 Wh kg −1, and power density of 250.18 W kg −1 at a current density of 1.0 A g −1 which was a considerable improvement over pristine and other doped samples. In addition, 15% Er doped ZnMnO3 preserved 98.39% of its initial capacitance during 2500 charge-discharge cycles at the highest current density of 5.0 A g −1 15% Er doped ZnMnO3 may maintain a significant amount of charge due to strong electrode-electrolyte contacts and anion-intercalated redox reactions.